2018
DOI: 10.1186/s40168-018-0450-3
|View full text |Cite
|
Sign up to set email alerts
|

Similarity of the dog and human gut microbiomes in gene content and response to diet

Abstract: BackgroundGut microbes influence their hosts in many ways, in particular by modulating the impact of diet. These effects have been studied most extensively in humans and mice. In this work, we used whole genome metagenomics to investigate the relationship between the gut metagenomes of dogs, humans, mice, and pigs.ResultsWe present a dog gut microbiome gene catalog containing 1,247,405 genes (based on 129 metagenomes and a total of 1.9 terabasepairs of sequencing data). Based on this catalog and taxonomic abun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
275
2
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 265 publications
(297 citation statements)
references
References 70 publications
19
275
2
1
Order By: Relevance
“…Previous studies on dog fecal shotgun metagenomics suggested that the canine gut microbiota resembles that from humans (11); more recently, Coelho and collaborators showed that canine gut microbiota resembles more to human gut microbiota than the most commonly used animal models, such as pig or mouse (12). Our results suggest another similarity: uncultured crAssphage was the most abundant virus in the fecal microbiota of one cohort of healthy dogs, similar to what has been previously reported in humans (13)(14)(15).…”
Section: Fecal Microbiota Of Healthy Dogssupporting
confidence: 88%
See 1 more Smart Citation
“…Previous studies on dog fecal shotgun metagenomics suggested that the canine gut microbiota resembles that from humans (11); more recently, Coelho and collaborators showed that canine gut microbiota resembles more to human gut microbiota than the most commonly used animal models, such as pig or mouse (12). Our results suggest another similarity: uncultured crAssphage was the most abundant virus in the fecal microbiota of one cohort of healthy dogs, similar to what has been previously reported in humans (13)(14)(15).…”
Section: Fecal Microbiota Of Healthy Dogssupporting
confidence: 88%
“…Until the date, two studies have characterized dog fecal microbiota using shotgun metagenomics, and both of them showed similarities to human gut microbiota (11,12). We aim to profile the canine fecal microbiota at lower taxonomical level -such as species-performing low deep metagenomics with Nanopore long-reads to complement the individual taxonomic profiles obtained with V4 16S rRNA sequencing.…”
Section: Introductionmentioning
confidence: 99%
“…villous atrophy and fusion). In severe cases, intestinal protein loss, similar to in human disease, can be observed [1,31,32]. This study has been carried out with EVs derived from canine cells and is of great value in facilitating subsequent experiments in dogs.…”
Section: Previous Studies Have Shown That Stem Cells Affect Recipientmentioning
confidence: 98%
“…As companion animals, dogs are 68 increasingly recognized as an ideal model system for translational gut microbiome research. In 69 addition to a harboring similar gut microbiota as humans, dogs often share their environment 70 with humans, consume a similar omnivorous diet, and can spontaneously develop GI disease 71 that shares many features in common with inflammatory bowel disease in humans (19)(20)(21)(22)(23)(24)(25)(26). In 72 addition, like humans, dogs frequently become infected with enteric parasites in early 73 life.…”
Section: Importance 23mentioning
confidence: 99%